EXPLORING (THAI HEART RESTAURANT’S) BUSINESS STRATEGY IN TAIPEI THROUGH SWOT AND PESTEL ANALYSIS: Universitas Budi Luhur Jakarta - Khalid, Zulvia; Fitri, Sara Aulia (PT. Media Edutama Nusantara, 2024)
This study Explores the business strategy of (Thai Heart Restaurant) in Taipei through comprehensive SWOT and PESTEL analysis. By Evaluating the Restaurant's strengths, weaknesses, opportunities, and threats, along with the Political, economic, social, technological, environmental, and legal factors influencing its operations, the research aims to provide a detailed understanding of the strategic positioning and competitive landscape. The Findings Highlight key areas for improvement and potential growth avenues, offering valuable insights for stakeholders to enhance the restaurant's market presence and overall performance in the dynamic Taiwanese culinary market through.